Faktor-Faktor Yang Mempengaruhi Niat Beli Mobil Low-Cost Green Car (LCGC) Di Kota Lhokseumawe - Suhendri, Suhendri Suhendri; Mariyudi, Mariyudi Mariyudi; ., T. Edyansyah (Jurnal Visioner & Strategis, 2024)
This study analyzes the influence of consumer attitudes, environmental knowledge, past behavior, environmental influence, labeling, and economic incentives on the purchase intention of low-cost green cars (LCGC) in Lhokseumawe City. This study uses the data collected through a survey method using a questionnaire as the data collection tool. The population in this study is 96 people who use LCGC. This study uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results indicate that consumer attitudes positively and significantly affect purchase intentions of LCGC in the Lhokseumawe city community, environmental knowledge positively and significantly affects purchase intentions of LCGC in the community in Lhokseumawe, and past behavior positively and significantly affects purchase intentions of LCGC in the Lhokseumawe city community. Social influence has a positive and significant effect on the intention to buy LCGC in the community in Lhokseumawe; labeling has a positive and significant effect on the intention to buy LCGC in the community in Lhokseumawe; but economic incentives do not have a positive and significant influence on the intention to buy LCGC in the Lhokseumawe city community. Simultaneously, consumer attitudes, environmental knowledge, past behavior, social influence, labeling, and economic incentives have a positive and significant effect on the intention to buy LCGC in the community of Lhokseumawe.  Keywords: attitudes, knowledge, behavior, environmental, labeling, economic incentives, and purchase intention